How water works - Ren, Corinna; Zimmer, Kristen (Exploring Spokane, 2020)
Jules and Oliver embark on an exciting new adventure when they encounter an unexpected challenge: their water supply suddenly stops! Determined to find answers, the two friends set out on a journey that leads them to the fascinating world of the City of Spokane Water Works.